Do Sex, Age, and Marital Status Influence the Motivations of Amateur Marathon Runners? The Poznan Marathon Case Study - León-Guereño, Patxi; Tapia-Serrano, Miguel Angel; Castañeda-Babarro, Arkaitz; Malchrowicz-Mośko, Ewa (Frontiers in Psychology, 2020)
The purpose of this research was to describe reasons for participating in a marathon and their association with marital status, age and sex. Four hundred and ninety-three runners in total, 144 of whom were women and 349 were men, completed the Polish version of the Motivations of Marathoners Scale (MOMS), containing 9 dimensions, and which was released through an online survey, in the Poznan marathon in Poland (2019). Athletes’ age (ranges 19-25, 26-35, 36-50, 51-70 years) and marital status (single, married, divorced) were asked of the participants. The results showed that statistical significant associations were found between athletes’ motivational aspects and athletes’ sex and age. To this end, three MOMS dimensions were statistically associated with athletes’ sex, a further three dimensions were different age-wise, and, lastly, marital status did not show differences in any of the dimensions. Moreover, statistical differences were not found in the multivariate analysis comparing marital status, sex and age range according to MOMS. Recreational runners’ reasons for participating in a marathon are different depending on certain socio-demographic variables; therefore, these characteristics should be considered when addressing different athletes in order to provide them with the most suitable information for taking part in such events.